Mapping Quranic Exegesis Research: Trends, Contributions, And Future Directions - Nirwana AN, Andri; Dahliana, Yeti; Rhain, Ainur; Nugroho, Kharis; Nurrahim, Ahmad; Azizah, Alfiyatul; Daud, Zainora (SCAD Independent, 2025)
This study explores the development and trends in Quranic exegesis research based on publications indexed in the Scopus database between 1994 and 2023. The research aims to provide a comprehensive understanding of the patterns, themes, and contributions in this field while highlighting areas for future scholarly exploration. Utilizing advanced data analysis tools, including Ms. Excel, R/R-Studio, and VOSviewer, the study examines key aspects such as publication growth, institutional contributions, author productivity, and thematic focus. The findings reveal significant growth in Quranic exegesis research since 2009, with the highest number of publications recorded in 2022. Malaysia emerges as the leading contributor, with Universiti Malaya identified as the most active institution. The results also indicate a shift in thematic focus, integrating modern topics such as religious moderation, social media, and discourse analysis alongside traditional areas like Quranic interpretation and linguistics. Despite these advancements, the study identifies a limited level of international collaboration, with fewer than 6% of publications involving cross-national authorship. This highlights the need for more significant global partnerships to enrich perspectives and foster innovation in Quranic studies. The insights provided by this study offer a valuable reference for researchers and institutions, paving the way for future advancements in Quranic exegesis research.